FireProt: web server for automated design of thermostable proteins - Musil, Milos; Stourac, Jan; Bendl, Jaroslav; Brezovsky, Jan; Prokop, Zbynek; Zendulka, Jaroslav; Martinek, Tomas; Bednar, David; Damborsky, Jiri (Nucleic acids research, 2017)
There is a continuous interest in increasing proteins stability to enhance their usability in numerous biomedical and biotechnological applications. A number of in silico tools for the prediction of the effect of mutations on protein stability have been developed recently. However, only single-point mutations with a small effect on protein stability are typically predicted with the existing tools and have to be followed by laborious protein expression, purification, and characterization. Here, we present FireProt, a web server for the automated design of multiple-point thermostable mutant proteins that combines structural and evolutionary information in its calculation core. FireProt utilizes sixteen tools and three protein engineering strategies for making reliable protein designs. The server is complemented with interactive, easy-to-use interface that allows users to directly analyze and optionally modify designed thermostable mutants. FireProt is freely available at http://loschmidt.chemi.muni.cz/fireprot.
Keywords: Protein Stability; uživatelské rozhraní počítače; internet; mutace; konformace proteinů, beta-řetězec; proteinové inženýrství; User-Computer Interface; interakční proteinové domény a motivy; stabilita proteinů; Structure-Activity Relationship; Thermodynamics; Protein Conformation, beta-Strand; Bacteria; Hydrolases; Protein Engineering; konformace proteinů, alfa-helix; Databases, Protein; hydrolasy; Internet; molekulární modely; vztahy mezi strukturou a aktivitou; Protein Interaction Domains and Motifs; Models, Molecular; termodynamika; lidé; Humans; Protein Conformation, alpha-Helical; Mutation; databáze proteinů